Search for fungi with potential mycoparasitic activity on causal agents of rust. - Doris Judith Luna Escalona; Dionicio Alvarado-Rosales; Armando Equihua-Martínez; Tomás Martínez-Trinidad; Andrés Quezada-Salinas; Soledad Vásquez-Murrieta; Jessica Solís-Ramírez; Abigail Jardines-Martínez; Matthew King; Roberto Noguez-Hernández; Ernestina Valadez-Moctezuma (Society for Indonesian Biodiversity, 2025)
Climate change has increased the incidence and severity of damage related to phytopathogens in agricultural and forestry production, resulting in a loss of 10-15% of the global production of major crops and adding up to hundreds of billions of dollars of additional costs across both industries (Chatterjee et al., 2016). Phytopathogenic fungi are responsible for 70% to 80% of these adverse effects (Savary et al., 2019). To reduce these losses, producers have resorted to the use of chemical fungicides for disease control, which has, in turn, favored the development of chemoresistance to these compounds in phytopathogens. Therefore, searching for alternative management strategies, such as using mycoparasitic fungi, is a crucial endeavor in the global effort to protect crops from phytopathogens. In this context, our research team used white rust as the disease agent in Chrysanthemum morifolium plants at the maximum level on the severity scale, with the afflicted leaf area ranging from 56 to 88%. After three months of treatment with Trichodema asperelloides TX19, a strain native to Mexico, demonstrated a reduction of 89% of the disease signs.